MTUN offers a bachelors’ degree programme in technology - UMP, PNC (2019)
Malaysia Technical University Network (MTUN) members comprising four public universities - Universiti Malaysia Pahang (UMP), Universiti Tun Hussein Onn Malaysia (UTHM), Universiti Teknikal Malaysia Melaka (UTeM) and Universiti Malaysia Perlis (UniMAP) made history with the introduction of the bachelor’s degree programme in technology (Bachelor of Technology – B. Tech.) that would have its first batch of students in September.